Makna Pesan Dakwah Komunikasi Visual Pada Akun Instagram “@qomikin” (Analisis Semiotika Charles Sanders Peirce) - Bagus Prasetya; Rubino Rubino; Andini Nur Bahri (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
This study aims to determine the meaning of visual communication da'wah messages contained in uploads of the Instagram account @qomikin in terms of Charles Sanders Peirce's semiotic analysis in which there are 3 illustrative images of each of the main messages of da'wah namely faith, sharia, and morality so that the total images studied totaling 9 illustrative images. The type and research approach used is a qualitative method with a semiotic analysis approach. The data analysis technique used is Charles Sanders' semiotic analysis. The systematics of analyzing illustrative images includes the selection of illustrative images and then used as signs, then the signs found are then used as objects, and finally the objects that have been found in the illustrative images are interpreted and conclusions are drawn about the meaning of the da'wah messages. Aqidah includes the problem of monotheism which doubts Allah SWT as the provider of sustenance for His servants, thinks too much about worldly problems so that they forget to remember death, and finally, humans are sinners and Allah SWT's forgiveness is so wide for His servants who want to repent. Then the sharia-themed da'wah messages include riya issues or showing off good deeds to others through social media, always being tabayyun towards all news or information received, and finally, gentleness is a measure of the quality of a human being. Then lastly, the moral-themed da'wah message includes the problem of a person whose prayers want to be answered immediately but his obligations to God are not carried out optimally, humans as creatures who like to complain but are in a hurry and are even reluctant to pray, and lastly, the luck of humans who do tahajud and the virtues or benefits derived from the midnight prayer. The illustration images and subheadlines used by the Instagram account @qomikin are interrelated and very relevant to the da'wah message conveyed by the da'wah account owner.